A differential fed wideband base station antenna with director and U‐shaped slot. Issue 12 (25th October 2022) - Guo, Jin Wen; Chu, Qing‐Xin
Abstract: In this article, a wideband base station antenna is designed. A new resonant mode is introduced into the antenna. Finally, four U‐shaped slots are added to the dipole of the antenna, and the antenna's third resonant mode is close to the first two resonant modes, which makes the antenna achieve wideband performance. The antenna is fabricated, and its performance is measured. The results show that the antenna has stable gain and radiation patterns. At the same time, the antenna works at 1.6–3.85 GHz with an impedance matching of −14 dB, and the relative bandwidth is 82%, the polarization isolation of the proposed antenna is better than −40 dB.